ACCOUNTING DEVELOPMENTS IN THE ATOMIC ENERGY ENTERPRISE. - Black, Martin L. (The Accounting Review, 1952)
Because the major job of constructing weapons is generally publicized as the primary function of the U.S. Atomic Energy Commission, (AEC) people in general do not realize how many other facets there are to AEC activities and few accountants know what a challenge it has presented to their profession. 'The Atomic Energy Act of 1946 provides that, "subject at all times to the paramount objective of assuring the common defense and security, the development and utilization of atomic energy shall, so far as practicable, be directed toward improving the public welfare, increasing the standard of living, strengthening free competition in private enterprise, and promoting world peace." Fortunately, these broad objectives are related. Most of the accomplishments of AEC are useful not only for defense but for peacetime purposes. Much accounting effort is required for the various types of research undertaken through AEC financing. Although this research is directed primarily to improving the processes for producing the materials that AEC is in business to manufacture, large sums are also expended for medical research and basic scientific research.